The case of sulfonation in the chemical synthesis of oligonucleotides. - Kraszewski, A (1980)
The sulfonation of nucleosidic component, a side reaction during phosphotriester bond formation, as a function of the reactivity of the condensing agents and the kind of substituents in the starting phosphodiester is discussed. It was found that in the coupling reaction of nucleoside alkyl phosphodiesters, the degree of sulfonation of the nucleosidic component was very high; while under the same conditions when the aryl group was present in the corresponding phosphodiester, this side reaction practically did not occur.